1998
DOI: 10.1097/00004694-199811000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Talectomy is recommended as a primary or salvage procedure for management of rigid or recurrent equinovarus deformity in arthrogryposis. Twenty-one feet (11 children) that had undergone talectomy were reviewed at a mean follow-up of 11.1 years (range, 2-24). Fourteen (73.7%) feet were satisfactory at final review, whereas five (26.3%) had an unsatisfactory result. Attention to technical details and accurate positioning of calcaneus in the ankle mortise are the two important prerequisites to guarantee a satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Most authors agreed that this method was effective, especially in cases of recurrent deformity, with the rate of satisfactory results reported to be as high as 70% 23,24,30,31,38 . Mild recurrent equinus or forefoot adduction was observed after some talectomies, but these recurrences rarely caused trouble in everyday living and did not constitute an indication for further operative treatment 23,24,30,31 . Poor outcomes after talectomy generally were considered to be the result of operative technical errors.…”
Section: Talectomymentioning
confidence: 94%
See 4 more Smart Citations
“…Most authors agreed that this method was effective, especially in cases of recurrent deformity, with the rate of satisfactory results reported to be as high as 70% 23,24,30,31,38 . Mild recurrent equinus or forefoot adduction was observed after some talectomies, but these recurrences rarely caused trouble in everyday living and did not constitute an indication for further operative treatment 23,24,30,31 . Poor outcomes after talectomy generally were considered to be the result of operative technical errors.…”
Section: Talectomymentioning
confidence: 94%
“…This goal of treatment remains true today; however, there are important recent developments-specifically, the need to consider patient satisfaction and the need to limit the number and extent of operative interventions. D'Souza et al underlined that, in cases of arthrogrypotic clubfoot, the presence of mild equinus and mild forefoot deformity are still compatible with a good result 23 . Cassis and Capdevila included patients' opinions in the final assessment of treatment and reported that a pain-free foot with the possibility of wearing standard shoes and overall patient satisfaction were enough to merit a good result despite the presence of mild residual deformity (up to 5°of equinus on clinical examination) 24 .…”
Section: Prevalence and Treatment Aimsmentioning
confidence: 99%
See 3 more Smart Citations